2022
DOI: 10.1186/s13567-022-01058-5
|View full text |Cite|
|
Sign up to set email alerts
|

HA gene amino acid mutations contribute to antigenic variation and immune escape of H9N2 influenza virus

Abstract: Based on differences in the amino acid sequence of the protein haemagglutinin (HA), the H9N2 avian influenza virus (H9N2 virus) has been clustered into multiple lineages, and its rapidly ongoing evolution increases the difficulties faced by prevention and control programs. The HA protein, a major antigenic protein, and the amino acid mutations that alter viral antigenicity in particular have always been of interest. Likewise, it has been well documented that some amino acid mutations in HA alter viral antigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Coding mutations in HA and NA proteins of the studied H9N2 viral genome confirmed continuing evolution within the G1 lineage. In general, the amino acid mutations at HA and NA proteins are functionally involved in antigenic shift or drift, virulence, binding ligands, viral oligomerization interfaces, escape mutants, creating or removing a potential N-glycosylation site, drug binding or resistance, and other biological properties of the circulating strains [ 28 , 29 ]. However, a significant number of mutations in the currently studied isolates were found in the potential antigenic sites of the HA protein that may alter its antigenic properties and contribute to vaccinal escape ( Table 1 ; Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coding mutations in HA and NA proteins of the studied H9N2 viral genome confirmed continuing evolution within the G1 lineage. In general, the amino acid mutations at HA and NA proteins are functionally involved in antigenic shift or drift, virulence, binding ligands, viral oligomerization interfaces, escape mutants, creating or removing a potential N-glycosylation site, drug binding or resistance, and other biological properties of the circulating strains [ 28 , 29 ]. However, a significant number of mutations in the currently studied isolates were found in the potential antigenic sites of the HA protein that may alter its antigenic properties and contribute to vaccinal escape ( Table 1 ; Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], we have been informed that author Huoying Shi has been incorrectly affiliated.…”
mentioning
confidence: 99%
“…In addition, the spike L452R mutation conferred SARS-CoV-2 escape from the immune system ( 25 ). Our findings suggested that Ags were often not recognized by Ab when other residues replaced antigenic residues K, L, or T. Correspondingly, the A180V mutation in the influenza virus promotes the virus to escape from Ab-based immunity ( 26 28 ). V483A mutation in SARS-CoV-2 was resistant to some neutralizing antibodies ( 29 ).…”
Section: Discussionmentioning
confidence: 78%